J. Murdoch Mitchison. 11 June 1922—17 March 2011. (12th December 2019) - Fantes, Peter; Mitchison, Sally
Abstract : John Murdoch Mitchison, known as Murdoch, was elected FRS in recognition of his work on the cell cycle. This emerged from a lifelong interest in the natural sciences, interrupted by war-time work in Operational Research which developed his critical appraisal of research technique. Post-war, he completed a PhD at Cambridge, then worked with Sir Michael Swann FRS (1962) on mitotic membrane changes in sea urchins. In 1953 Murdoch joined the University of Edinburgh Zoology Department and in time switched his interest to the fission yeast Schizosaccharomyces pombe . Over the next 30 years he investigated cell growth and division, employing a meticulous approach to experiments. He considered there to be a 'growth cycle' in cells, independent of the DNA-division cycle. There is experimental evidence to support this idea, but further investigations of it have been limited. Actively fostering a relaxed but industrious and enquiring ethos in the lab, Murdoch ran the department jointly with Aubrey Manning. The Mitchison group's work at Edinburgh attracted students including Paul Nurse (later Sir Paul Nurse; FRS 1989, PRS 2010–2015), Béla Novak, Kim Nasmyth (FRS 1989) and Peter Fantes as well as many visiting academics. Murdoch's work on S. pombe came to both national and international recognition, forming a foundation for the current thriving community of researchers in cell physiology, cell genetics and molecular biology. Murdoch is remembered for his single-minded commitment to cell biology research and his generous, fair-minded support of younger colleagues and students. He was, additionally, an expert landscape gardener, a convivial host and phenomenally well-informed on most subjects.